Target approach to treating osseous system pathology - M. B. Stenina; A. D. Petrova (Опухоли женской репродуктивной системы)
ВTo maintain the normal status of the osseous system in cancer patients is an important task of practical oncology as the complications associated with skeletal pathology substantially worsen quality of life in the patients, increase the cost of treatment, and can affect their lifespan. Osseous complications must be prevented not only in patients with skeletal metastatic lesion, but also in healthy individuals cured from cancer, who may have a significant reduction in bone density (osteoporosis) as a complication due to antitumor therapy. Along with bisphosphonates that are well-known and traditionally used in this situation, there have today been target drugs (denosumab) that can be effective in monitoring the osseous system and preventing the complications of osteoporosis and skeletal metastatic lesion.